Restructuring service at a mastology outpatient clinic during the COVID-19 pandemic - Cristina Poliana Rolim Saraiva dos Santos; Ana Fátima Carvalho Fernandes; Denise Montenegro da Silva; Régia Christina Moura Barbosa Castro
ABSTRACT Objective: to report the experience of a health team in restructuring service at a mastology outpatient clinic. Methods: an experience report in a public university service mastology outpatient in Ceará between March and April 2020. Service in this outpatient clinic is exclusively for women and who have breast changes for surgical treatments ranging from nodulectomies to mastectomies with oncoplastic. Results: increased COVID-19 cases brought the need to restructure healthcare services. The following steps were followed: identification of scheduled patients, reading of clinical developments in electronic medical records, individual assessment to define whether or not appointment would remain, telephone contact to inform about unscheduling. Among the 555 consultations scheduled for March and April 2020, 316 (56.9%) were maintained. Final considerations: restructuring consultations at a mastology outpatient clinic optimized the waiting time for consultations and avoided crowds at service, providing patient safety.